Sensitivity optimisation of hybrid calixarene-reduced graphene oxide langmuir-blodgett thin films via langmuir, optical, structural and elektrical characterisations - Lim, Darwina Choo Kheng (2020)
The study aimed to investigate the characteristics of calixarene, reduced graphene oxide(rGO) and their composite in order to optimise the sensitivity of the composite. The calixarenes(calix[4]arene, calix[6]arene and calix[8]arene) and rGO were prepared in solutionto form a Langmuir film by using Langmuir-Blodgett (LB) trough. The values of 30 mN/m and15 mN/m were selected for calixarenes and rGO respectively for the thin film deposition. Thesurface potential (?V) and effective dipole moment (?) of calixarenes were alsoinvestigated. The optical properties of calixarene in solution and thin film were studied using UV-Visible (UV-Vis) spectroscopy and compared to ensure the stability ofthe thin film. Meanwhile, the rGO thin film was characterised with UV-Vis spectroscopy for theoptical property, Raman spectroscopy for the crystallinity and four-point probe for theelectrical property to obtain current-voltage (I-V) characteristics, resistivity, andconductivity. Field Emission Scanning Electron Microscopy (FESEM) was used to observe thesurface morphology of calixarene and rGO thin films. Then, both the materials were fabricated intovarious types of calixarenes-rGO composites using the LB technique. Same characterisationprocedures were applied to the newly formed composites using UV-Vis spectroscopy, Ramanspectroscopy, four-point probe, and FESEM. Results showed that the addition of rGO inthe fabrication of calixarene thin-film has improved the electrical property of thecomposite as calixarene is a non-conductive material. The structural and optical properties investigation also showed good structural and stable thin film formedfrom both materials. Calix[8]arene-rGO composited with 6 layers of rGO is thebest-fabricated composite, as shown from the characterization process. As a conclusion, thisstudy implies that rGO plays a significant role in improving the conductivityperformance of calixarene, thus giverise to the further potential of calixarene in sensing application.